STUDENTS’ PERCEPTIONS TOWARD SMALL GROUP DISCUSSION ON READING COMPREHENSION SKILLS AT THE ELEVENTH GRADE OF SMK NEGERI 2 PANYABUNGAN - Risna Hanani Lubis; Dina Syarifah; Sri Wahyuni Hasibuan (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This study aimed to explore students' perceptions of Small Group Discussion on Reading Comprehension Skills for learning English. The subject of research were 34 students from SMK Negeri 2 Panyabungan. Data was collected through observation, interviews and documentation. This research used qualitative method with case study design. This study used semi structured interviews as the data collection method. The interview data were analyzed using Miles and Huberman's flow model. The were two findings show that students used small group discussion on reading comprehension Skills in English. The first findings was students have positive perception toward small group discussion on reading comprehension skills. The second findings was students have several challenges they were, 1) lack of time for discussion, 2) lack of participation with the group, 3) differences of opinion within the group and 4) lack of vocabulary.